2013
DOI: 10.12720/jolst.1.3.180-183
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Ascomycetous Fungi, Neosartorya spp. and Screening for Its Antibacterial Metabolites

Abstract:  Abstract-The aim of the present study was to identify ascomycetous fungi (Neosartorya spp.) and examined the antibacterial activities of crude mycelium extracted by ethyl acetate from these fungal genera. Among 10 ascomycetous fungal isolates, Neosartorya sp., were screened from soil and showed a broader antimicrobial spectrum than the other. Especially, fungal strain KKU-1NK1 showed strongly antibacterial activities. This fungal strain was belonging to Neosartorya spinosa which was identified using 5.8S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…The dendrogram of calmodulin gene was demonstated representative of these fungi (Figure 3). Our result was supported with findings of Sanmanoch et al [4] who reported the nucleotide sequences from the ITS region is useful and suitable for Neosartorya identification. However, identification of Neosartorya should be using both molecular and morphological techniques [12].…”
Section: Isolation Morphological and Dna Sequencing Characterizationsupporting
confidence: 93%
See 3 more Smart Citations
“…The dendrogram of calmodulin gene was demonstated representative of these fungi (Figure 3). Our result was supported with findings of Sanmanoch et al [4] who reported the nucleotide sequences from the ITS region is useful and suitable for Neosartorya identification. However, identification of Neosartorya should be using both molecular and morphological techniques [12].…”
Section: Isolation Morphological and Dna Sequencing Characterizationsupporting
confidence: 93%
“…Crude extracts from Neosartorya showed well inhibited the growth of gram positive bacteria (B. subtilis, S. aureus and M. luteus) ( Table 2). Our result was supported with findings of Sanmanoch et al [4] who reported to the antibacterial activities of crude ethyl acetate extract from N. spinosa KKU1NK1 most strongly inhibited the growth of gram positive pathogenic bacteria (S. aureus, S. saprophyticus, S. pneumonia and B. subtilis).…”
Section: Antimicrobial Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…[28][29][30][31]. However, P. citrinum with antimicrobial and antiyeast activities was reported from Surat Thani province in southern part of Thailand [32].…”
Section: B Determination Of Antimicrobial Activity Of Pkf121mentioning
confidence: 99%